2017
DOI: 10.1002/brb3.641
|View full text |Cite
|
Sign up to set email alerts
|

BRAF‐V600E immunohistochemistry in a large series of glial and glial–neuronal tumors

Abstract: IntroductionSome glial–neuronal tumors (GNT) (pleomorphic xantho‐astrocytoma [PXA], ganglioglioma [GG]) display BRAF‐V600E mutation, which represents a diagnostic clue to these entities. Targeted therapies against BRAF‐V600 protein have shown promising results in GNT. The aim of this study was to assess the utility of BRAF‐V600E immunohistochemistry (IHC, clone VE1) in daily practice in a series of 140 glial, and GNT compared to molecular biology (MB) techniques.MethodsWe performed BRAF‐V600E IHC on all 140 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…positive rate such as GC/GG(35/47, 74.5%)and P-CPG 14/14, 100%) had high speci city and sensitivity in immunohistochemical detection when further veri ed by Real-time PCR (49/49, 100%). BRAF V600E positive rate of GC/GG was 74.5%, which was similar to that reported by Schindler [9] . Among the 35 cases with BRAF V600E mutation, 10 cases showed cytoplasmic positive in only a small number of ganglion cell-like tumor cells (10/35, 28.6%), and there was no case…”
Section: Histopathological Features and Immunoreactivity Pattern Of Bsupporting
confidence: 90%
See 1 more Smart Citation
“…positive rate such as GC/GG(35/47, 74.5%)and P-CPG 14/14, 100%) had high speci city and sensitivity in immunohistochemical detection when further veri ed by Real-time PCR (49/49, 100%). BRAF V600E positive rate of GC/GG was 74.5%, which was similar to that reported by Schindler [9] . Among the 35 cases with BRAF V600E mutation, 10 cases showed cytoplasmic positive in only a small number of ganglion cell-like tumor cells (10/35, 28.6%), and there was no case…”
Section: Histopathological Features and Immunoreactivity Pattern Of Bsupporting
confidence: 90%
“…However, few studies have assessed the reliability of anti-BRAF-V600E immunohistochemistry (IHC) in brain tumors. Breton has examined the expression of BRAF VE1 in a series of neuroepithelial neoplasias, but the sensitivity and speci city of immunohistochemical detection of BRAF-V600E mutant protein were not evaluated due to the fact that some of the tissue samples were not insu cient for further con rmation by molecular assay [9] . The aim of this study was to assess the utlity of BRAF-V600E IHC compared to molecular biology on a large series of CNS tumors, in order to provide a useful reference for the use of BRAF-V600E IHC in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Our cohort included mostly adult patients (91.8% of cases, median age 28 years, range: 18-76); hence, discrepancies as to the frequency of BRAF mutations between the cited findings [17,32,36] and these presented here may be also related to this fact, apart from an obvious reason related to a low number (n = 15) of GG cases. In turn, a different pattern [16] or no association between patient age and BRAF V600E mutation [35,40] has been found for pilocytic astrocytoma. In this context, Gierke et al have shown that V600E mutations in PA were very scarce in the pediatric age group (2%; 1/45) and were limited to the middle age group (13%; 3/23) [16].…”
Section: Discussionmentioning
confidence: 96%
“…The gold standard for BRAF mutation analysis is molecular biology (DNA-based) techniques, with classical Sanger sequencing being the most commonly used [41,42]. However, in the case of CNS tumors, in particular ganglioglioma, the relevance of the latter method has recently been questioned [40,43], due to its high detection threshold of 20% allele frequency, which does not work well with a low number and/or scattered distribution of neoplastic cells [44]. Although other molecular biology techniques, such as pyrosequencing, next-generation sequencing, PNA-clamping PCR, ddPCR, and ASqPCR, have higher sensitivity (detection of 0.02-10% mutant in a background of wild type), all DNA-based methods are often expensive, labor-intensive, time-consuming, and not widely available in pathology laboratories, also because they require a highly skilled operator and complex infrastructure [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to KIAA1549–BRAF , other BRAF fusion partners were also found in PAs, including FAM131B , RNF130 , CLCN6 , MKRN1 , GNAII, and GIT2 . [ 10 ] Besides, activating point mutation BRAF V600E occurs in a small part of PAs, especially in the supratentorial locations, [ 11 ] whereas it is the most common finding in papillary craniopharyngiomas, PXA, gangliogliomas (GG) and DNT. [ 11 ] Moreover, aberrant DNA methylation has been studied in PAs, which varied according to tumor locations as well.…”
Section: Discussionmentioning
confidence: 99%